Indicators of Human Management: Key Success Factor in the Strategic Human Resources Management by: Giovanni Hernández and Haward Ibarguen (GEON Journal (Management, Organizations and Business), 2014)
The indicators of human management has become as noted Beltran (1998) in "Vital Signs" that show the health of companies learning, ie, evaluate qualitative and quantitative strategic variables associated with effectiveness and productivity, and based results, making for Strategic Management of Human Resources with higher probability of success are made, because they will be aligned to the strategy. These indicators of human management are an integral part of the management information systems as a competitive factor that managers use to perform the function of planning and control that seeks to achieve the objectives.
Keywords: Management; Planning and Control; Indicators for Human Resources; Competitiveness; Productivity